A Systematic Literature Review of Thematic LKPD Media to Enhance Narrative Text Analysis Skills in Elementary Education - Epita Dewi Purnama Fajrin; Herlina Usman; Apit Dulyapit (Journal of General Education and Humanities, 2026)
Reading comprehension, particularly in analyzing narrative texts, remains a challenge for many elementary school students because they use limited structured and engaging instructional media. Conventional teaching practices often fail to guide students in systematically identifying narrative elements such as characters, settings, plots, and main ideas. Therefore, this study aims to examine the role of thematic literacy Student Worksheets (LKPD) as instructional media in improving elementary students’ reading comprehension of narrative texts. This research employed a Systematic Literature Review (SLR) method following PRISMA guidelines. Relevant articles were collected from Google Scholar, Scopus, and ERIC, focusing on publications between 2020 and 2025. The selected studies were screened using predetermined inclusion and exclusion criteria, followed by data extraction and qualitative synthesis to identify patterns of findings across studies. The review results indicate that thematic literacy LKPD effectively supports reading comprehension by providing structured tasks, guided questions, and contextual learning activities. These features help students systematically analyze narrative elements and encourage active participation, collaborative discussion, and critical thinking. The findings also show that LKPD use contributes to more meaningful and interactive literacy learning experiences in elementary classrooms. In conclusion, thematic literacy LKPD serves as an effective instructional medium for enhancing elementary students’ narrative reading comprehension when implemented with appropriate instructional design.